Two series of Ln-MOFs by solvent induced self-assembly demonstrating the rapid selective sensing of Mg2+ and Fe3+ cations. Issue 43 (3rd November 2020) - Wang, Xiaokang; Wang, Yutong; Wang, Xia; Lu, Kebin; Jiang, Weifeng; Cui, Pei-Pei; Hao, Hongguo; Dai, Fangna
Abstract : Two Eu-MOFs synthesized by a solvent-induced self-assembly strategy demonstrate selectively sensing of Mg 2+ and Fe 3+ cations. Abstract : Two series of lanthanide-based metal–organic frameworks, namely [Ln(BIPA-TC)0.5 (DMA)2 (NO3 )]·DMA·H2 O n (1-Ln, Ln = Eu, Dy, Sm, Nd) and [Ln2 (BIPA-TC)1.5 (DMA)3 (H2 O)2 ]·2DMA·2H2 O n (2-Ln, Ln = Eu, Dy, Sm, Nd), were successfully constructed via a solvent regulation strategy based on a π-electron rich tetra-carboxylate ligand (H4 BIPA-TC). 1-Ln shows a 4-connected lvt topology with the point symbol of 4 2 ·8 4 , but 2-Ln displays a new 4, 4, 6-connected wxk1 topology with the point symbol of 4 3 ·8 3 4 4 6 ·6 6 ·8 3 2 8 6 . The solid-state luminescence property and the microporous nature of Eu-MOFs (1-Eu and 2-Eu ) indicate that they can potentially be used as luminescent sensors. Fluorescence measurements indicate that Fe 3+ exhibits the quenching effect for 1-Eu with the quenching efficiency of 93.1%. 2-Eu is the first MOF sensor for Mg 2+ with the lowest detection limit of 1.53 × 10 −10 mol L −1 and displays good recyclable capability. Simultaneously, in the presence of other metal ions (Ca 2+, Mn 2+, Co 2+, Ni 2+, Cu 2+, Zn 2+, Cd 2+, Pd 2+, Al 3+, Cr 3+ and Fe 3+ ), 2-Eu can maintain the selective sensing of Mg 2+, indicating its potential for Mg 2+ turn-on sensing.